Multichannel time-domain measurements for EMI filter optimization - Nemashkalo, Daria (2024)
The current energy crisis has kicked off a rapidly changing energy sector that requires society to become more sustainable. One aspect of which is regarding electrical energy, and its conversion. The number of power electronic dependent products is increasing, creating a complex electromagnetic environment (EME), often resulting in interoperability problems.